PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASI DAN KEADILAN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. RADITYA DEWATA PERKASA CANGGU - Ni Kadek Indah Pebrianti; I Nengah Sudja; Yenny Verawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Employee job satisfaction is a person's attitude towards the results of his work which is determined by the difference between all that is expected and all that is felt from the work he receives. The purpose of this study is to analyze leadership, organizational commitment and organizational justice affect employee job satisfaction. The object of this research is the influence of leadership, organizational commitment and organizational justice on employee job satisfaction at PT. Raditya Dewata Perkasa Canggu. In this study, the population was 68 employees. In this study, the researcher used the study population, so the number of samples was the same as the total population, namely 68 people. Collecting data using a questionnaire. Data analysis used multiple linear regression analysis. The result of the research is that leadership has a positive and significant effect on employee job satisfaction at PT. Raditya Dewata Perkasa. Organizational commitment has a positive and significant effect on employee job satisfaction at PT. Raditya Dewata Perkasa Canggu. Organizational justice has a positive and significant effect on employee job satisfaction at PT. Raditya Dewata Perkasa.